Dogmatism, Materialism and Faith in Graham Greene’s Prose - Bohdan Vysloužil (American and British Studies Annual, 2015)
This article deals with materialism, religious dogmatism and faith in Graham Greene’s novels The Power and the Glory (1940), The Heart of the Matter (1948), and the short story “The Hint of an Explanation” (1954). The aim of the paper is to elucidate the nature of the author’s attitude to the relation between faith, logical reasoning and urges for material wants. For the purposes of delineating some of the basic philosophical, social and psychological principles concerning faith, logical reasoning and materialism the article aims at providing an explanation based on theories developed by Søren Kierkegaard, Karl Marx and Abraham Maslow.